Treatment of gestational diabetes diagnosed by the IADPSG criteria decreases excessive fetal growth - Kyoung-Hee Lee; You-Jung Han; Jin-Hoon Chung; Moon-Young Kim; Hyun-Mee Ryu; Jin-Ha Kim; Dong-Wook Kwak; Sung-Hoon Kim; Seongwoo Yang; Minhyoung Kim (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveWe evaluated the effect on treatment using the new International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria for gestational diabetes mellitus (GDM) diagnosis.MethodsSingleton pregnant women whose plasma glucose levels were ≥140 mg/dL on the 50 g glucose challenge test (GCT) underwent 75 g oral glucose tolerance for GDM diagnosis. During the first half of the study period, GDM was diagnosed using 2 abnormal values by Carpenter-Coustan (C-C) criteria. In the second half of the study period, 1 or more abnormal values by IADPSG criteria were used for GDM diagnosis. Pregnant women were classified into 5 groups: normal 50 g GCT, positive 50 g GCT but non-GDM, GDM by IADPSG criteria and non-treated, GDM by IADPSG criteria and treated, GDM by C-C criteria and treated. The odds ratios (ORs) for large for gestational age (LGA) and macrosomia were analyzed.ResultsOf the 2,678 patients, the frequency of GDM diagnosed by C-C and IADPSG criteria was 2.6% and 7.5%. ORs (95% confidence intervals [CIs]) for LGA and macrosomia in the group with GDM by IADPSG criteria and non-treated were 2.81 (95% CI, 1.47-5.38) and 2.84 (95% CI, 1.08-7.47). The risk of LGA and macrosomia did not increase in the group with GDM by IADPSG criteria and treated.ConclusionThe risk of LGA and macrosomia for mild GDM diagnosed solely by IADPSG criteria depends on whether they are treated or not. Treatment of GDM based on IADPSG criteria reduces the risk of excessive fetal growth.Trial RegistrationClinical Research Information Service Identifier: KCT0000776